Combined impacts of climate change and human activities on blue and green water resources in a high-intensity development watershed - X. Tan; B. Liu; X. Tan; X. Tan; Z. Huang; J. Fu (Hydrology and Earth System Sciences)
Sustainable management of blue and green water resources is vital for the stability and sustainability of watershed ecosystems. Although there has been extensive attention paid to blue water (BW), which is closely related to human beings, the relevance of green water (GW) to ecosystem security is typically disregarded in water resource evaluations. Specifically, comprehensive studies are scarce on the detection and attribution of variations of blue and green water in the Dongjiang River basin (DRB), an important source of regional water supply in the Guangdong–Hong Kong–Macao Greater Bay Area (GBA) of China. Here we assess the variations of BW and GW scarcity and quantify the impacts of climate change and land use change on BW and GW in DRB using the multi-water-flux calibrated Soil and Water Assessment Tool (SWAT). Results show that BW and green water storage (GWS) in DRB increased slowly at rates of 0.14 and 0.015 mm a−1, respectively, while green water flow (GWF) decreased significantly at a rate of −0.21 mm a−1. The degree of BW and GW scarcity in DRB is low, and the per capita water resources in more than 80 % of DRB exceed 1700 m3 per capita per year. Attribution results show that 88.0 %, 88.5 %, and 39.4 % of changes in BW, GWF, and GWS result from climate change. Both climate change and land use change have decreased BW, while climate change (land use change) has decreased (increased) GWF in DRB. These findings can guide the optimization of the allocation of blue and green water resources between upper and lower reach areas in DRB and further improve the understanding of blue and green water evolution patterns in humid regions.